The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4236/ojbm.2017.54051
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Entrepreneurial Intentions of University Students: Applying the Theory of Planned Behaviour in Zambia, Africa

Abstract: The current paper contributes to the entrepreneurial intention (EI) literature by applying the theory of planned behaviour (TPB) in a developing African country with unique socio-economic and cultural context. Thus it examines the influence of social norms, personal attitudes and perceived behavioural control on business start-up intentions. Based on a quantitative approach, primary survey data were collected from 306 final year undergraduate students at a public university. The data were analyzed using correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
6
14
0
1
Order By: Relevance
“…The current findings show that EIM explains the EI quite well with the least variance reported in Saudi Arabia. A study on Zambia [134], which is a collectivist society, also confirmed the same results. A comparative study of Poland and South Africa [108] confirmed the validity of TPB in samples from both countries.…”
Section: Discussionsupporting
confidence: 66%
“…The current findings show that EIM explains the EI quite well with the least variance reported in Saudi Arabia. A study on Zambia [134], which is a collectivist society, also confirmed the same results. A comparative study of Poland and South Africa [108] confirmed the validity of TPB in samples from both countries.…”
Section: Discussionsupporting
confidence: 66%
“…Thirdly, the paper explores EI of final year students in Zambia and therefore represents a valuable contribution to African entrepreneurship research. Besides a few studies on Africa such as in South Africa (Malebana and Swanepoel, 2014;Urban, 2006Urban, , 2012) and in Ethiopia (Gerba, 2012), extant literature reveals that research on EI, nascent behaviour and self-efficacy is mainly conducted in developed countries; developing countries, especially Africa, and that includes Zambia, are under-researched (Fayolle and Liñán, 2014;Hoskisson et al, 2011;Liñán and Fayolle, 2015;Mwiya et al, 2017). This constrains generalisability of the prior research conclusions.…”
Section: Contributions and Practical Implicationsmentioning
confidence: 99%
“…Where also, an individual was more likely to start a business if they initiated by a close person (Otuya et al, 2013;Angriawan et al, 2012;Mueller, 2011). This was because if an individual perceives gained from the immediate social setting would approve his/her decision, the prospect of social, emotional and other support would provide extra stimulus to effort the entrepreneurial activity (Mwiya et al, 2017). For a collectivist society like Yemen, the opinions of people to the individual was considered as an important in his/her life to be a business start-up.…”
Section: Discussionmentioning
confidence: 99%